Pengaruh Profitabilitas Terhadap Manajemen Laba dengan Ukuran Perusahaan Sebagai Moderasi - Lili Panggih Rahayu (JURNAL EKOBIS DEWANTARA, 2018)
This study aimstodeterminetheeffectofProfitabilityto Profit Managementismoderatedby Company Size. The population in thisresearchismanufacturingcompanyofindustrialandchemical sub sectorlisted in Indonesia Stock Exchange (BEI). The sample in thisresearchismanufacturingcompanywhichislisted in Indonesia Stock Exchange (BEI), especiallybasicindustryandchemistryfromyear 2014 until 2016. Sourcesof data used in thisresearchissecondary data. Data analysismethod in thisresearchisSimple Linear RegressionandModeratedRegresionAnalysis (MRA). The resultsshowedthatProfitabilitahave a positiveandsignificanteffecton Profit Management. Thiscanbeprovedfromthesignificancevalueof 0.00 <0.05 andthevalueof t arithmetic> t table (4.410> 1.6833). Company sizeisabletomoderatetherelationshipProfitabilityto Profit Management. Ukura Company strengthenstherelationshipProfitabilityto Profit Management. Thiscanbeprovenfromthesignificancevalueof 0,000 <0,05 andthevalueof t arithmetic> t table (237,481> 1,6833).